Suppose 2*t + 2*l - 2 = -0, 2*l + 3 = -t. Let q be 2⁄5 + 23/t. Let c be 2/(-5) - (-17)/q. Solve 0 = -i + c*i for i.
0
Suppose -2*q + q = -4*y + 5, 0 = -3*y - 2*q - 10. Solve -t + 1 - 2 = y for t.
-1
Let w be -3 + (-5 - -3 - -5). Solve -4 = -y - w for y.
4
Let h = 23 + -23. Solve h = 5*u - 0*u for u.
0
Let a(g) = -2*g + 19. Let o® = 1. Let m(w) = -a(w) + 6*o(w). Let l be m(10). Solve -l = -3*z - 1 for z.
2
Suppose j + 6*a + 8 = 2*a, -5*a = -3*j + 10. Solve 2*h - 6*h = j for h.
0
Let a(f) = f - 3. Let x© = c - 1. Let y(u) = a(u) - 3*x(u). Let b be y(-2). Solve 0 = -b*r + 4 - 24 for r.
-5
Let g(x) be the third derivative of 1⁄24*x4 + 0*x3 - x2 + 1⁄30*x6 + 0*x + 0 + 0*x**5. Let a be g(1). Solve h + 0 + a = 0 for h.
-5
Suppose -2*g - 4 = -20. Let o = 0 - -1. Let l be o - 3 - (-5 - -3). Solve l = 4*j - 0*j + g for j.
-2
Let u(m) = m3 - 7*m2 + 7*m - 2. Let p be u(6). Suppose 6*n = p*n. Solve -2*t + n - 10 = 0 for t.
-5